The The repetition and the instant in Kierkegaard: : an interweaving of concepts - Paula, Marcio Gimenes de (2017)
Kierkegaard, Repetição, Instante, Cristianismo, Filosofi a grega. Abstract. In the great work of Kierkegaard there are two important concepts: the repetition and the instant. According to the Danish author, these concepts are Greek, but must be analyzed from the Christianity perspective too. The purpose of this article is to analyze these concepts in two of Kierkegaard’s works: The Repetition and Philosophical Fragments.